Bullying victimization depressive symptoms and suicidal behaviors among students at secondary schools in Mwanza city north-western Tanzania: a cross-sectional study - Tabitha Bubinza; Matiko Mwita; Robert Kitambo; Antony Kapesa (Discover Psychology)
Abstract Background Approximately 40% of students worldwide are involved in bullying as either bully, victims or both. Bullying in schools can have a devastating impact on bullies and victims leading to depression, and even suicide. Like other parts of the world, Tanzania is suffering from bullying in its secondary schools but there is a lack of data about the prevalence, associated factors and outcome of bullying in Tanzania, the gap this study aims to fill. Methods This was a descriptive cross-sectional study design involving four hundred and sixty-nine students at secondary schools in Mwanza Northern-Western Tanzania. Data were collected using researcher-designed social-demographic questionnaire, the Adolescent Peer Relations Instrument (APRI), Patient Health Questionnaire-9 (PHQ-9), and Suicidal Behaviors Questionnaire-Revised (SBQ-R). A multi stage sampling technique was used to recruit schools and participants in September 2023. Results A total of 469 participants were enrolled with mean age of 14.11 years (± 1.13 SD), ranging from 10 to 20 years. Majority of the participants were below 15 years, with female to male ratio of almost 1:1. The study found that 66.75% of students experienced bullying victimization, with a mean victimization score of 32.6 (SD 13.41), while 52.45% reported engaging in bullying behaviors, with a mean score of 27.94 (SD 9.33). About 42.65% exhibited depressive symptoms, and Suicidal behaviors were noted in 10.45% of the participants. Bullying victimization was significantly associated with increased odds of both depressive symptoms (AOR 2.7, 95% CI: 1.7–4.3, P < 0.001), and suicidal behaviors (AOR 2.2, 95% CI: 1.9–5.1, P = 0.046). Conclusion About half of the participants are in the high-level bullying group. About two-fifth of the participants had depressive symptoms, and nearly one-tenth of the participants had Suicide ideations with bullying been the commonest significantly associated factor for both depressive symptoms and suicide behaviors. The findings underscore the need for comprehensive anti-bullying programs be implemented in schools, with accessible mental health resources.